Microencapsulation Technology of Ginger Oleoresin With Chitosan as Wall Material: A review - Jayanudin , , Rochmadi, Moh. Fahrurrozi, Sang Kompiang Wirawan (Journal of Applied Pharmaceutical Science, 2016)
Ginger oleoresin is a product of ginger extraction using an organic solvent. Ginger oleoresin can be used in the pharmaceutical and food industry because it tastes the same as the original material, but more concentrated and also contains active components such as shogaol, gingerol which are sensitive to environmental influences so easily oxidized. Appropriate protection for ginger oleoresin is by microencapsulation. Microencapsulation is the process of protecting the active ingredient in the form of gas, liquid and solid by the use of coating material. The main objective was for the protection of microencapsulated active ingredients and release control by controlling the dissolution rate of the coating material. Microencapsulation method can be done in physics such as spray drying or chemically as coacervation. The type of coating used is not toxic, biocompatible and biodegradable polymers such as chitosan which is natural and safe for consumption. Rate of release can be done by determining the release kinetics using several models such as the model of zero order, first order, Higuchi models, Korsmeyer-Peppas and Hixon-Crowell.
Keywords: Coacervation, Chitosan, Ginger oleoresin, Microencapsulation, Spray drying.